New definition of high blood pressure. Are we ready? - Yanque Robles, Omar Fernando (2018)
The new Guide for the Prevention, Detection, Evaluation and Management of Arterial Hypertension in Adults of the ACC / AHA (American College of Cardiology / American Heart Association), published on November 13, 2017, has reclassified the degrees of hypertension arterial (table 1). This guide is an update of the publication of the National Heart, Lung and Blood Institute "Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation and Treatment of Arterial Hypertension" (NHLB, JNC 7) of the year 2003 (1).